2002
DOI: 10.3354/meps225053
|View full text |Cite
|
Sign up to set email alerts
|

Overfishing drives a trophic cascade in the Black Sea

Abstract: During recent decades, environmental conditions have deteriorated in the Black Sea. Population explosions of phytoplankton and jellyfish have become frequent and several fish stocks have collapsed. In this study, literature sources and long-term data are explored in order to find empirical evidence for ecosystem effects of fishing. Inverse trends of decreasing predators, increasing planktivorous fish, decreasing zooplankton and increasing phytoplankton biomass are revealed. Increased phytoplankton biomass prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
242
0
9

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(259 citation statements)
references
References 32 publications
8
242
0
9
Order By: Relevance
“…As the above examples have demonstrated, recent examinations of the roles of spatial heterogeneity and the movement of marine populations have implications for the initiation and detection of regime shifts, and some common features emerge. Based on spatio-temporal analyses within the Benguela, Baltic and Black Seas, seasonal and/or interannual shifts in the spatial distribution of predatory populations have contributed to initiating regime shifts and may explain shifts in associations between key population dynamics and environmental drivers [37,49,52,53]. In the North Sea [38] and Barents Sea [39], spatial downscaling of population models relating environmental and predation dynamics on key species have illustrated that relationships such as the apparent increased role of predation at lower water temperatures, first reported in among-system comparisons [40], are mirrored at smaller spatial scale orders of magnitude (figures 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the above examples have demonstrated, recent examinations of the roles of spatial heterogeneity and the movement of marine populations have implications for the initiation and detection of regime shifts, and some common features emerge. Based on spatio-temporal analyses within the Benguela, Baltic and Black Seas, seasonal and/or interannual shifts in the spatial distribution of predatory populations have contributed to initiating regime shifts and may explain shifts in associations between key population dynamics and environmental drivers [37,49,52,53]. In the North Sea [38] and Barents Sea [39], spatial downscaling of population models relating environmental and predation dynamics on key species have illustrated that relationships such as the apparent increased role of predation at lower water temperatures, first reported in among-system comparisons [40], are mirrored at smaller spatial scale orders of magnitude (figures 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…In the Black Sea, a pronounced regime switch from a predator-dominated to a planktivore-dominated system has been documented [52,53]. As described by Aristotle in his Historia Animalium [54], the main pelagic predators (bonito, bluefish and mackerel, but also bluefin tuna in the past) migrate in the spring from the southern Black Sea and Mediterranean to feed during the warm season along the most productive area of the basin-the large and shallow northwest shelf.…”
Section: Spatial Variation In Dominant Driversmentioning
confidence: 99%
“…Quoy et J.P. Gaimard, A. Reid and C.R. Johnson, unpublished datax, and generalist predators in pelagic (e.g., the ctenophore Mnemiopsis leidyi, Shiganova 1998, Daskalov 2002, 2003 and benthic (e.g., Northern Pacific seastar, Asterias amurensis A. Agassiz; Ross et al 2003) habitats. All of these animals have the capacity to effect deleterious impact on richness, diversity and ecosystem functioning over large spatial scales.…”
Section: Consequences Of Invasionsmentioning
confidence: 99%
“…Apex marine predators are a key component of this ecosystem, because they regulate the demography of species at lower trophic levels through a top-down regulation of the trophic food-web (4,7,8,11). Modeling studies have suggested that the recent decimation of these predators in the Black Sea was a key factor in reducing ecosystem resilience, inevitably leading to its reorganization (i.e., a regime shift) (7,8,10,11).…”
mentioning
confidence: 99%